Penguatan Daya Saing UMKM Melalui Transformasi Digital dan Revitalisasi Branding - Pipin Fitriasari; Muhammad Sauqi Sazeli; Kurnia Fauziah; Masya Delfia Ananda; Sakha Lutfia (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
There has been slow development and the competitiveness of MSMEs in general is still limited. Where most MSMEs are only able to produce, but have not been able to market their products better. This weak marketing is not only a market issue, but many other aspects directly and indirectly influence it so that many MSME businesses are slow to develop. Therefore, this community service activity is carried out with a program to increase the competitiveness of MSMEs. This was carried out in Klandasan Ilir Village, Balikpapan City District, where the strengthening activity was carried out through a seminar by inviting MSMEs in RT 39 and RT 43. The target or target of this activity is MSME actors, who already have businesses or PKK cadres who want to start their businesses. Where these MSME actors still have limitations in marketing their products on social media. With this activity, it is hoped that it can develop and motivate MSME actors to develop their businesses, so that MSME products will be better known. Efforts to increase the competitiveness of MSMEs through digital transformation and branding revitalization. With digital transformation and branding revitalization, MSMEs can build their product brands and be able to compete in the market. MSMEs also provide brief training on basic product photography techniques, such as shooting from above and from the side to enhance product details. This training also helps MSMEs improve their skills in creating digital content in the form of product photos or videos.